2019
DOI: 10.5005/jp-journals-10015-1647
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Infection Control Barrier on Cross Contamination and its Effect on the Intensity Variation

Abstract: Aim: To compare and assess the level of infection control provided by a cling film against a sleeve and their impact on the light intensity level of dental light-emitting diode (LED) light-curing units (LCUs). Materials and methods: A sleeve and a cling film of proprietary brands were compared on their reduction of light output and bacterial colonies on agar plates. Including a control group, 120 samples of analog radiometer readings were obtained. A total of 90 samples, including 10 each for positive and nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Enzyme-linked immunosorbent assay (ELISA) was the method used in most of the studies (41.6%). Eleven studies (46%) showed that the oral cavity of caries-free individuals present higher s-IgA concentration (17,27,31,52,62,68,75,79,90,99,107). Higher s-IgA concentration was found in the oral cavity of caries-affected individuals by eight studies (33%) (14-16, 43, 63, 88, 102, 105).…”
Section: Qualitative Synthesismentioning
confidence: 98%
“…Enzyme-linked immunosorbent assay (ELISA) was the method used in most of the studies (41.6%). Eleven studies (46%) showed that the oral cavity of caries-free individuals present higher s-IgA concentration (17,27,31,52,62,68,75,79,90,99,107). Higher s-IgA concentration was found in the oral cavity of caries-affected individuals by eight studies (33%) (14-16, 43, 63, 88, 102, 105).…”
Section: Qualitative Synthesismentioning
confidence: 98%